The Use of Drainage Structures in Abdominal Surgery in the Postoperative Period (Experimental Study) - I. A. Shurygina (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
Preventive drainage of the abdominal cavity after gastrointestinal surgery is widely used. However, debates about the need for abdominal drainage have not subsided so far.The aim of the study: to establish the effect of the duration of the use of drains on the development of postoperative complications in the experiment.Materials and methods. For the experiments, male Wistar rats weighing 220-250 g at the age of 9 months were used. A mid laparotomy was performed, then the serous-muscular layer of the cecum was opened, 1 cm long, followed by suturing the wound with a self-twisting suture, and the parietal peritoneum of the right lateral canal was sized 1.5х1.5 cm. A silicone catheter was installed. The study was conducted in two groups. In the first group, the drainage was removed after 24 hours, in the second - after three days. The study was conducted on the 3rd, 7th, 14th and 30th day, 6 animals in each group/at each term. The severity of the adhesive process in the abdominal cavity, the presence of an inflammatory process in the peritoneum, and hematological parameters were evaluated.Results. It was established that the severity of the adhesion process in groups in all periods of observation was comparable. The severity of purulent-inflammatory processes in the abdominal cavity on the 14th and 30th day was significantly lower when installing drainage for 1 day than 3 days.Conclusion. A study with the installation of drainage in the absence of infection of the peritoneum showed that the duration of the installation of the drain adversely affects the incidence of purulent-inflammatory changes in the abdominal cavity, which must be taken into account when planning the use of drainages in abdominal surgery.